UNDERSTANDING THE BEAUTY OF CHILDRENS’ SCRATCHES - Kamsidjo Budi Utomo (Universal Journal, 2020)
Children love to draw in any place without fear of being wrong (Oitjinsan). Connoisseurs are often fascinated by the children’s scratches. On the other hand, community generally does not understand where the beauty is. Drawings act as the symbols of the children’s deepest feelings. The thickness of the lines shows the nuances of the idea of a story that was experienced. Drawing means exploring the imaginations, thoughts, feelings and ideas of the environment. The urge to express through non-appearing words makes the scratches in the drawing becomes more meaningful. Drawing is a process of imagination that is expressed in the form of lines, colors and textures. Thus, scratch as an art product has fulfilled the requirements of artistic techniques and expressions. That is why understanding the beauty of the scratches is important.